Guilt, Uncertainty, Education Needs, and Knowledge of Mothers With Children Experiencing Precocious Puberty - Hye Young Ahn RN, PhD; Kyung Hee Yoo RN, MSN; Mi Ryeong Song RN, PhD (SAGE Publishing, 2022)
Introduction. Childhood illnesses not only affect the child, but also the family members. Objective. The purpose of this study was to investigate the guilt, uncertainty, education needs, and knowledge of mothers with children experiencing precocious puberty. Methods. Data were collected in August, 2017. The participants of the study were the mothers of children experiencing precocious puberty. A total of 111 copies of questionnaires were collected. Descriptive statistics, independent t -test, one-way ANOVA, Pearson's correlation coefficient were used for the analysis, using the SPSS 24.0 program. Results. Mothers of children experiencing precocious puberty require psychological interventions that can alleviate their guilt and uncertainty, as well as enhance their knowledge of the emotional support needed by their children. Conclusion. Mothers with children experiencing precocious puberty had a high level of education needs to know, but the knowledge they knew was insufficient. Future studies need to focus on developing education programs for mothers dealing with their child's precocious puberty.